(untitled) (International Journal of Food and Nutritional Sciences, 2021)
In order to investigate the impact of bonding, bridging, and connecting social capital on happiness in Europe, this research uses a Multilevel Structural Equation Model (GSEM) to analyze data from the European Social Survey. We investigate the relationship between well being and societal and individual levels of social capital, accounting for the hierarchical nature of the data across many nations. According to our research, the social capital that fosters close-knit relationships—bonding social capital—has the most beneficial impact on happiness. Linking and bridging social capital—that is, creating relationships that are hierarchical and larger, respectively—also greatly enhances well-being. Furthermore, the findings show significant cross-national differences in these effects, indicating that the national context is critical to the link between social capital and happiness. These findings highlight how crucial it is to promote diverse types of social capital in order to improve both individual and societal well-being across Europe.